COMPARATIVE STUDY OF SCHOOL CURRICULUM AFFILIATED TO TURKEY AND EGYPT IN PATI DISTRICT IN THE NATIONAL EDUCATION PERSPECTIVE - MUHAMAD FARID BASYARI (Proceeding Of The International Seminar and Conference on Global Issues, 2020)
AbstractEducation in Indonesia is currently not fully able to form a generationexcellent youth and character. The majority of schools only focus on transferring knowledge without educating their character so that they become good according to the teachings of the Prophet Muhammad SAW. so that with the integration of the Islamic boarding school curriculum and the madrasah curriculum it is hoped that it will be able to form a generation that is khaira ummah (intellectual, spiritual and character human beings). The research problem is the form of integration of the Islamic boarding school curriculum and the madrasah curriculum, implementation, evaluation, and the impact of curriculum implementation on national education. This study uses a qualitative-descriptive-analytic method, with data collection techniques: observation, interviews and documentation. In testing the validity of the data using triangulation and member check. and on data analysis methods using data reduction, data presentation, conclusions and verification. Keywords: Curriculum Integration, Implementation, National Education AbstractEducation in Indonesia is currently not fully able to form a young generation of superior and character. The majority of schools only focus on transferring knowledge without educating their characters to be good in accordance with the teachings of the Prophet Muhammad. so that with the integration of the Islamic boarding school curriculum and the madrasa curriculum, it is hoped that it will be able to form a generation that is khaira ummah (intellectual, spiritual and characterful people). The research problem is the form of integration of the Islamic boarding school curriculum and madrasa curriculum, implementation, evaluation, and the impact of curriculum implementation on national education. This study uses a qualitative-descriptive-analytic method, with data collection techniques: observation, interviews and documentation. In testing the validity of the data using triangulation and member check. and the data analysis method using data reduction, data presentation, conclusion and verification.Keywords: Curriculum Integration, Implementation, National Education